The structure of melittin in the form I crystals and its implication for melittin's lytic and surface activities. - Terwilliger, T C (1982)
Melittin from bee venom is water-soluble, yet integrates into membranes and lyses cells. Each melittin chain consists of 26 amino acid residues and in aqueous salt solutions it exists as a tetramer. We have determined the molecular structure of the tetramer in two crystal forms grown from concentrated salt solutions. In both crystal forms the melittin polypeptide is a bent alpha-helical rod, with the "inner" surface largely consisting of hydrophobic sidechains and the "outer" surface consisting of hydrophilic side chains. Thus, the helix is strongly amphiphilic. In the tetramer, four such helices contribute their hydrophobic side chains to the center of the molecule. The packing of melittin tetramers is also very similar in the two crystal forms: they are packed in planar layers with the outsides forming hydrophilic surfaces and the insides (the centers of melittin tetramers) forming a hydrophobic surface. We suggest that the surface activity of melittin can be rationalized in terms of these surfaces. The lytic activity of melittin can also be interpreted in terms of the molecular structure observed in the crystals: the hydrophobic inner surface of a melittin helix may integrate into the apolar region of a bilayer with the helix axis approximately parallel to the plane of the bilayer, and with the hydrophilic surface exposed to the aqueous phase. This integration would be expected to disrupt the bilayer because of melittin helix would penetrate only a short distance into it. Additionally, the integration of melittin from one side of a bilayer would produce a surface area difference across the bilayer, perhaps leading to lysis. In this view, melittin is distinct from membrane proteins that penetrate evenly into both leaflets of a bilayer or exactly halfway through a bilayer, and hence we refer to melittin as a surface-active protein.